Modelation of groundwater in oil palm plantations and grasslands across geophysic technics - Sánchez-García, María Dolores; Bolaina-Vazconcelos, Jonathan; Chávez-Hernández, Guillermo; Damas-López, Daniel Andrés; Estrada-Botello, Maximiano Antonio; Mendoza-Palacios, Juan de Dios; Sánchez-Hernández, Rufo (Ecosistemas y Recursos Agropecuarios, 2021)
A research was carried out during the rainy season, with the aim of characterizing through electrical resistivity tomography (ERT), the distribution of groundwater in three areas cultivated with oil palm (Elaeis Guineensis Jacq.) of 5, 11 and 25 years old, and were compared respect to grassland adjacent. In each area, 5 profiles were made with a dipole-dipole arrangement in a NE-SW direction, covering 40 meters of grassland and 80 meters within the plantations, with electrodic separation of 5 meters, and 20 meters between profiles. Through an IRIS INSTRUMENT Syscal Junior resistivity meter, the distribution of electrical resistivity was calculated from a large number of measurements of subsoil apparent resistivities, that allowed to generate an electrical image that shows the distribution of the true resistivity of the subsoil. In each line, the data inversion was carried out through the Res2Dinv software, to generate a 2D model, where an electrical resistivity pattern is observed from highest to lowest depending on the depth of the ground, which implies the presence of sands, silts, alluvium, clays and gravel in throughout the area. The level of the saturated zone is deeper in oil palm plantations than in grasslands, particularly in plantations of 25 years old. It is concluded that, despite the seasonal rains, the saturation zone in the subsoil is deeper in oil palm plantations than in grasslands, which suggests that the crop can remove more water than the adjacent grasslands.